Quality of life and psychosocial aspects in Greek patients with psoriasis: a cross-sectional study - Anargyros Kouris; Christos Christodoulou; Christina Stefanaki; Miltiadis Livaditis; Revekka Tsatovidou; Constantinos Kouskoukis; Athanasios Petridis; George Kontochristopoulos (Sociedade Brasileira de Dermatologia, 2015)
Abstract: BACKGROUND: Psoriasis is a common, long-term skin disease associated with high levels of psychological distress and a considerable adverse impact on life. The effects of psoriasis, beyond skin affliction, are seldom recognized and often undertreated. OBJECTIVE: The aim of the study is to evaluate the quality of life, anxiety and depression, self-esteem and loneliness in patients with psoriasis. METHODS: Eighty-four patients with psoriasis were enrolled in the study. The quality of life, depression and anxiety, loneliness and self-esteem of the patient were assessed using the Dermatology Life Quality Index, Hospital Anxiety and Depression Scale, the UCLA loneliness Scale (UCLA-Version 3) and Rosenberg's Self-esteem Scale, respectively. RESULTS: The Dermatology Quality of Life Index score among psoriasis patients was 12.61 ± 4.88. They had statistically significantly higher scores according to the Hospital Anxiety and Depression Scale -anxiety subscale (p=0.032)-compared with healthy volunteers. Moreover, a statistically significant difference was found between the two groups concerning the UCLA-scale (p=0.033) and RSES-scale (p<0.0001). Female patients presented with lower self-esteem than male patients. CONCLUSION: Psoriasis is a distressing, recurrent disorder that significantly impairs quality of life. Therefore, the recognition and future management of psoriasis may require the involvement of multi-disciplinary teams to manage the physical, psychological and social aspects of the condition, as is the case for systemic, long-term conditions.